KECEMASAN BERBAHASA ASING (BAHASA ARAB) - Mamdukh Budiman (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2015)
This paper is the development and dynamics of a second language (second language) is growing andgrowing complexity of the problem. Changes in language functions not only as a symbol of themeaning and role of language itself. Foreign language or unfamiliar called Second Language separateposition of the main language of a community that is on the plains just a second language, in otherwords that a foreign language has become a stigma in society that desperately needed foreign languageand foreign language only as an additional language course. Arabic is a second language (second language) of the Indonesian national language or evena third language after English are certainly more dominant in its use. The use of foreign languages,especially Arabic, those who have never completely make its own difficulties than ever learnedalthough the plateau region of Religious functional. Because the general assumptions of society thatlearning Arabic for religious study, not as the language required in the professional worl d with theexception of professional educators and Arabic religion itself, in addition to the general assumptionsmentioned above, the existence of stigma and stereotypes in the general public, that the Arabiclanguage difficulty of the grammatical and vocabulary. Learning a foreign language or second language (second language) for the beginner evenamong expert (advanced) require extra effort and thought, especially when faced with the indicatorsor achievements success in learning Arabic, then there is an emotional effect and anxiety or anxious.And not just on the plains of the learning process, but when faced with situations and conditionsthat should be required to use the Arabic language properly and smoothly. But indirectly also thepresence of anxiety, fear and anxiety when in a foreign language (Arabic) occurred mistakes. Givingrise to the psychological impact of a sense of fear and anxiety. When learning a language isaccompanied by feelings or unstable psychiatric (anxiety, panic and stress), the achievement oflanguage, learning a foreign language will decrease Keywords: Foreign, Second, Arabic, Anxiety, Profession, Nursing